Reengineering Analysis of Business Process System "Read Full Text On Screen" Institutional Repository - Hermawan, Sari (Edulib, 2022)
Scientific works produced by tertiary institutions are encouraged to be accessed online and openly through institutional repositories. This is motivated by various regulations from the government to prevent plagiarism and fulfil the public's information needs. The Indonesian University of Education Institutional Repository (UPI Repository), managed by the UPI Library during the COVID-19 Pandemic, experienced problems in providing access to limited collection data. Therefore this study aims to conduct a business process engineering analysis on the UPI Repository limited collection service so that it can be effectively and efficiently accessed by UPI academics so that they can contribute to the learning process. The business process reengineering analysis method refers to the System Development Life Cycle (SDLC) approach. The results of the research are that there are additional features in the UPI Repository, namely Full-text reading services, SSO login features, and Full-Text data display on-screen access features. Changes in the design of the business process have resulted in a reduction in the process, namely VPN access, before the UPI Repository. There has been an increase in users of the Read Full Text on Screen service after the new design changes were implemented.